Quality of life and the venous function of the lower limb after harvest of autologous external iliac vein grafts: a clinical follow-up study - Kaneoka, Yuji; Maeda, Atsuyuki; Sugimoto, Masayuki; Isogai, Masatoshi; Ishibashi, Hiroyuki (Surgery today (Tokyo, Japan), 2013)
Purpose To investigate the quality of life and venous function of the lower limbs after right external iliac vein (REIV) grafting for digestive surgery. Method The study subjects included 66 patients treated surgically for hepatopancreatobiliary malignancy who underwent concomitant resection with REIV for use as autologous grafts. Fifteen patients completed the Chronic Lower Limb Venous Insufficiency Questionnaire (CIVIQ), and the venous function was assessed using air plethysmography (APG) and duplex ultrasound in 10 patients. The outcomes of the 15 patients were analyzed statistically. Results Postoperative morbidity related to graft harvest occurred in three of the 66 patients (5 %). The right legs of the follow-up patients were 6 ± 3 % larger than the left legs. The mean CIVIQ score was acceptably low at 27; however, moderate symptoms (e.g., pain upon long-time standing or walking) occurred in seven of the 15 patients. APG revealed moderate to severe outflow obstructions that did not improve during long-term observation. The blood flow depicted on duplex ultrasonography was significantly associated with the patients’ symptoms. No deep venous reflux was encountered, and no right leg skin changes or venous claudication developed. Conclusions The symptoms occurring after REIV resection can be unexpectedly prolonged. These unfavorable effects must be kept in mind and the possible sequelae should be carefully explained to patients preoperatively.